Thyroid abnormality trend over time in Northeastern Regions of Kazakstan, adjacent to the Semipalatinsk Nuclear Test Site: a case review of pathological findings for 7271 patients - Zhumadilov, Zhaxybay; GUSEV, BORIS I.; TAKADA, JUN; HOSHI, Masaharu; Kimura, AKIRO; Hayakawa, Norihiko; Takeichi, Nobuo (Journal of Radiation Research, 2000)
From 1949 through 1989 nuclear weapons testing carried out by the former Soviet Union at the Semipalatinsk Nuclear Test Site (SNTS) resulted in local fallout affecting the residents of Semipalatinsk, Ust-Kamenogorsk and Pavlodar regions of Kazakstan. To investigate the possible relationship between radiation exposure and thyroid gland abnormalities, we conducted a case review of pathological findings of 7271 urban and rural patients who underwent surgery from 1966–96. Of the 7271 patients, 761 (10.5%) were men, and 6510 (89.5%) were women...
Keywords: nuclear weapon testing; Semipalatinsk; thyroid abnormalities; pathological specimens; radiationinduced neoplasms; Research Subject Categories::MEDICINE